NCOG-72. DIFFERENTIAL EFFECTS OF SURGERY AND CHEMOTHERAPY ON CHILDREN WITH POSTERIOR FOSSA BRAIN TUMORS. (9th November 2020) - Dhanani, Sofia; O'Neil, Sharon; Tanedo, Jeffrey; Malvar, Jemily; Tamrazi, Benita; Finlay, Jonathan; Trane, Francesca; Rajagopalan, Vidya; Lepore, Natasha; Nelson, Mary Baron
Abstract: BACKGROUND: Few neuroimaging studies of children with brain tumors treated with chemotherapy without radiation exist, and the neuropsychological effects of chemotherapy remain unclear. We aimed to differentiate the effects of surgery and chemotherapy on brain microstructure and cognition. METHODS: Twenty-eight children with a history of posterior fossa tumor (17 treated with surgery alone; 11 treated with surgery + chemotherapy), and 21 sibling controls (n= 49) underwent diffusion tensor imaging (DTI) and neuropsychological assessment a mean of 4.5 (surgery group) to 9 years (surgery + chemotherapy group) after treatment. Psychometric measures focused on general intelligence, executive functions, processing speed, learning and memory, and social-emotional functioning. Age at diagnosis and time since diagnosis were covariates in the analyses. Group differences in DTI findings and psychometric scores, and correlations between psychometric scores and DTI results were examined. RESULTS: Mean fractional anisotropy (FA) in the prefrontal cortex, white matter tracts, hippocampus, putamen, globus pallidus, thalamus, and pons were significantly (z≥ 2SD) lower in children treated with surgery + chemotherapy compared to those treated with surgery alone. In neuropsychological evaluation, the patient groups differed only in receptive vocabulary (p= 0.05), with children treated with surgery + chemotherapy scoring lower. Both patient groups scored lower than healthy sibling controls on measures of visuoconstructional reasoning (p= 0.02) and delayed visual (p= 0.02) and spatial memory (p= 0.01). Lower FA in the uncinate fasciculus and higher FA in the right thalamus associated with higher scores on general intelligence (p= 0.003, p= 0.002), and higher FA in the right thalamus associated with higher scores on spatial learning (p= 0.01) and memory (p= 0.01) in children treated with surgery + chemotherapy. CONCLUSIONS: Chemotherapy is associated with injury to the microstructure of white and gray matter and neuropsychological deficits not seen in children with posterior fossa tumors treated with surgery alone.